Correlação de medidas de glicosímetros e dosagem laboratorial - Maciel, Tavany Elisa Santos (2014)
The glucometer allows the measurement of glycemia to be performed by the user without hindering his daily routine. Two principles are used to measure the level of blood glycemia: photometric and amperometric. On the photometric principle, after biochemical reactions with the sample obtained from capillary venous blood, the glycemia is measured by changing the wavelength of a light beam pattern. On the amperometric principle, after the biochemical reactions with the capillary venous blood sample, intensity of eletric current flowing through the sample can be measured and evaluated, where the intensity of the electric current is proportional to the blood glycemia level. The glucometers available on the market use one of the mentioned principles. Equipment used by biochemical analysis laboratories do make use of the photometric principle with venous blood samples collected from the patient's forearm. This work, approved by the ethics committee, evaluates a set of glycemia measures made by multiple glucometers and laboratory measuring equipment used by clinical laboratories. Presented results demonstrated a strong correlation between glycemia measures obtained from glucometer and equipment used on biochemical analysis laboratories, but with a high rate of systematic and random errors. With the results, the usage of glucometers can be assured for personal and individual measurement of glycemia, whereas this kind of device cannot be used for diagnosis.